Comparative Analysis of Taper and Taperless Blade Design for Ocean Wind Turbines in Ciheras Coastline, West Java - Madi, Madi; Tuswan, Tuswan; Arirohman, Ilham Dwi; Ismail, Abdi (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2021)
The blade is the most critical part of turbine design because it is used to convert kinetic to mechanical energy. In general, the blade types used for ocean wind turbines are taper and taperless blades, like those operated at Ciheras Coastline. Previous research has been analyzed the type of airfoil used in designing taper blades for ocean wind turbines using NACA 4412, which was selected as the optimal foil configuration at sea wind speeds of 12 m/s. In this study, the comparison of taper and taperless blade designs using NACA 4412 at a wind speed of 12 m/s is analyzed. The comparative study with previous research has been carried out and resulted in the same graphical patterns and performance results. In this study, the focus is on investigating the performance coefficient of power, mechanical power, and electrical power. The final result shows that taper blade designs are highly recommended for use in ocean wind turbines compared to taperless blades. In general, the performance produced by taper blades is more significant than taperless blades at relatively high wind speeds. The maximum performance coefficient of power, mechanical power, and electrical power generated by the taper blades in sequent are 0.47, 1535 watts, and 786 watts, while the taperless blades have 0.44, 1437 watts, and 736 watts.